2023
DOI: 10.1021/acsanm.3c00321
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticle-Modified Tungsten Oxide Flakes as Nitric Oxide Sensor Electrodes for Fruit Quality Monitoring

Abstract: Development of low-cost, handheld nitric oxide (NO) sensors is very much important due to its major role in environmental pollution, biomedical research, and food safety applications. In this study, an electrochemical NO sensor has been fabricated using gold nanoparticle (Au NP)-modified tungsten oxide (WO 3 ) nanoflakes. WO 3 nanoflakes were grown hydrothermally on fluorine doped tin oxide (FTO) substrates, and Au NPs were attached by a photoreduction method. The sensing characteristics of pristine WO 3 and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The nanoprobe also showed high selectivity in the presence of other ROS and RNS like H 2 O 2 , ClO − , ONOO − , NO 2 − and NO 3 − . Other nanoparticle-based systems for NO sensing developed recently include probes based on Ce-based metal−organic framework 135 , aminoguanidine hydrochloride and citric acid-based carbon-dots 136 , 4-(((3-aminonaphthalen-2-yl)amino)methyl)benzoic acid functionalized CdTe/CdS/ZnS quantum dots 137 , electrochemically active gold nanoparticle-modified tungsten oxide (WO 3 ) nanoflakes 138 , or Au nanoparticles that undergo azide–alkyne click chemistry-mediated aggregation-based NO sensor 139 .…”
Section: No Sensorsmentioning
confidence: 99%
“…The nanoprobe also showed high selectivity in the presence of other ROS and RNS like H 2 O 2 , ClO − , ONOO − , NO 2 − and NO 3 − . Other nanoparticle-based systems for NO sensing developed recently include probes based on Ce-based metal−organic framework 135 , aminoguanidine hydrochloride and citric acid-based carbon-dots 136 , 4-(((3-aminonaphthalen-2-yl)amino)methyl)benzoic acid functionalized CdTe/CdS/ZnS quantum dots 137 , electrochemically active gold nanoparticle-modified tungsten oxide (WO 3 ) nanoflakes 138 , or Au nanoparticles that undergo azide–alkyne click chemistry-mediated aggregation-based NO sensor 139 .…”
Section: No Sensorsmentioning
confidence: 99%
“…12 It has been demonstrated that ultrathin WO 3 nanosheets can endow WO 3 with high conductivity and further improve the sensitivity of the sensor relative to bulk WO 3 . 13 Similarly, gold nanoparticles (AuNPs), as a common functional nanomaterial, have been widely used in the field of sensing attributed to their unique physicochemical properties, such as good chemical stability, high surface area, and fast electron transfer properties. [14][15][16] For example, Jin et al electrodeposited AuNPs onto a modified glassy carbon electrode surface and constructed a novel, sensitive and label-free aptasensor for ratiometric electrochemical sensing of dopamine.…”
Section: Introductionmentioning
confidence: 99%
“…Technologies for detecting and monitoring fruit volatiles include gas chromatography–mass spectroscopy (GC-MS), , electrochemical, colorimetric, e-nose, surface-enhanced Raman spectroscopy, optical, piezoelectric sensor, and organic field effect transistors . Standard GC-MS equipment and laser-based optical sensors, however, are often very expensive and are not appropriate for portable applications or on-site monitoring analyses.…”
Section: Introductionmentioning
confidence: 99%